SOSIALISASI BUDIKDAMBER SEBAGAI SALAH SATU UPAYA PENGUATAN KETAHANAN PANGAN RUMAH TANGGA SELAMA MASA PPKM AKIBAT PANDEMI COVID-19 - Fajria Noviana; Zaki Ainul Fadli; Nur Hastuti (Departemen Linguistik, Fakultas Ilmu Budaya Universitas Diponegoro, 2021)
The number of people whose income has decreased drastically due to the PPKM regulations in Indonesia as an effect of the covid-19 pandemic has contributed to the declination in food security. To maintain food security, it should not only be borne by the government but also requires synergy and efforts from the lowest levels in society, namely individuals and households. One of them is by utilizing the house yard in urban areas for urban farming as an alternative and solution for family food sources. One example of urban farming is the cultivation of vegetables and fish using the budikdamber method. This budikdamber method is very practical because it does not require a large area, so it can be made even in a narrow yard. In addition, budikdamber is relatively easy to manufacture and maintain, inexpensive, water-efficient, and the results can be enjoyed in a relatively short time.Keywords: budikdamber; food security; pandemic; covid-19